Suppression of Aldosterone Synthesis and Secretion by Channel Antagonists - Keiichi Ikeda; Tsuyoshi Isaka; Kouki Fujioka; Yoshinobu Manome; Katsuyoshi Tojo (International Journal of Endocrinology)
Aldosterone, a specific mineralocorticoid receptor (MR) agonist and a key player in the development of hypertension, is synthesized as a final product of renin-angiotensin-aldosterone system. Hypertension can be generally treated by negating the effects of angiotensin II through the use of angiotensin-converting enzyme inhibitors (ACE-Is) or angiotensin II type 1 receptor antagonists (ARBs). However, the efficacy of angiotensin II blockade by such drugs is sometimes diminished by the so-called “aldosterone breakthrough” effect, by which ACE-Is or ARBs (renin-angiotensin system (RAS) inhibitors) gradually lose their effectiveness against hypertension due to the overproduction of aldosterone, known as primary aldosteronism. Although MR antagonists are used to antagonize the effects of aldosterone, these drugs may, however, give rise to life-threatening adverse actions, such as hyperkalemia, particularly when used in conjunction with RAS inhibitors. Recently, several groups have reported that some dihydropyridine Ca2+ channel blockers (CCBs) have inhibitory actions on aldosterone production in in vitro and in the clinical setting. Therefore, the use of such dihydropyridine CCBs to treat aldosterone-related hypertension may prove beneficial to circumvent such therapeutic problems. In this paper, we discuss the mechanism of action of CCBs on aldosterone production and clinical perspectives for CCB use to inhibit MR activity in hypertensive patients.